2014
DOI: 10.1080/08905436.2014.963600
|View full text |Cite
|
Sign up to set email alerts
|

A Maltooligosaccharides Producing α-Amylase fromBacillus subtilisSDP1 Isolated from Rhizosphere ofAcacia cyanophyllaLindley

Abstract: Maltooligosaccharides producing amylases are required in the food industry, especially in breadmaking. The Bacillus subtilis strain SDP1 amylase hydrolyses starch to produce maltotriose and maltotetraose along with maltose after prolonged reactions of 5 h. Bacillus subtilis strain SDP1 was isolated from the rhizosphere of Acacia cyanophylla Lindley from the Çukurova region of Turkey. The highest enzyme production was achieved with soluble starch as the carbon and yeast extract as the nitrogen source and at pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…5). For carrier-limited materials, the quantum efficiency could be enhanced by inserting a layer that effectually transport electrons from the cathode and so this will improve the performance of optoelectronic devices [39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5). For carrier-limited materials, the quantum efficiency could be enhanced by inserting a layer that effectually transport electrons from the cathode and so this will improve the performance of optoelectronic devices [39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Resultsmentioning
confidence: 99%
“…Taxonomic characterization of strain was determined by using morphological, physiological and molecular methods such as 16S rRNA analysis [41]. The sequence has been submitted to the genbank with the accession number HM235916.…”
Section: Synthesis and Characterization Of Aunpsmentioning
confidence: 99%
“…The acidstable, thermostable and Ca 2+ -independent amylases reduce the cost and time required for multistep MOS production from raw starches ( Sharma et al, 2016 ). To date, several amylases have been reported with optimum pH activity at 4–7 ( Khemakhem et al, 2009 ; Asoodeh et al, 2010 ; Sharma and Satyanarayana, 2013 ; Ozturk et al, 2014 ). However, the acid stability, Ca 2+ independence, thermostability, raw starch saccharification and a very high K cat value of Ba-Gt-amy make it distinct from others.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, Rahmani et al (2013) found maltose and maltotriose produced by amylase of Brevibacterium sp. using black potato starch as substrate, while amylase of Bacillus subtilis strain SDP1 isolated from rhizosphere of Acacia produces maltotriose and maltotetraose (Ozturk et al 2014). Furthermore, Abdul-Manas et al (2014) reported that amylase of an alkaliphilic Bacillus lehensis G1 could degrade oligosaccharides by producing maltooligosaccharides with a higher degree of polymerization than maltoheptaose observed on thinlayer chromatography and high-performance liquid chromatography analyses.…”
Section: Analysis Of Hydrolysed Products By the Selected Bacterial Am...mentioning
confidence: 99%